Pengaruh Self Control Dan Self Regulated Learning Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SMK Negeri 5 Kota Bengkulu - Feby Wahyuni (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2023)
Abstract: The purpose of this studi is to find out : 1) The effect of self control on student achievement in the subject of Islamic Religious Education at SMK Negeri 5 Bengkulu City, 2) The effect of self regulated learning on student achievement in the subject of Religious Education. Islam at SMK Negeri 5 Bengkulu City, 3) The effect of self control and self regulated learning on student achievement in Islamic Religious Education subjects at SMK Negeri 5 Bengkulu City. This studies uses quantitative type of research with an ex post facto approach. The population of this studies amounted to 564 students, a sample of 85 students. The sampling technique used was probability sampling with the type of proportionate stratified random sampling. Data collection techniques using questionnaires, documentation, and observation. The results showed that: 1) There was a significant influence between self control (X1) on student achievement in Islamic Religious Education subjects (Y) at SMK Negeri 5 Bengkulu City. This can be seen from the value of tcount > ttable (2.124 > 1.988) with a regression coefficient of 0.134 which contributes 13.4% to student learning achievement (Y), 2) There is a significant effect between self regulated learning (X2) on learning achievement students in the subject of Islamic Religious Education (Y) at SMK Negeri 5 Bengkulu City. This can be seen from the value of tcount > ttable (1.997 > 1.988) with a regression coefficient of 0.114 which contributes 11.4% to student learning achievement (Y), 3) There is a significant effect between self control (X1) and self regulated learning (X2) on student achievement (Y) at SMK Negeri 5 Bengkulu City. This can be seen from the value of Fcount > Ftable (4.627 > 3.10) with a coefficient of determination of 0.079 which contributes 7.9% to student achievement (Y), or it can be seen from the multiple linear regression equation Y = 66.652 + 0.134X1 + 0.114X2 + 0.05.Keywords : Self Control, Self Regulated Learning, Student Achievement Abstrak : Penelitian ini bertujuan untuk : 1) Mengetahui apakah ada pengaruh self control terhadap prestasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di SMK Negeri 5 Kota Bengkulu, 2) Mengetahui apakah ada pengaruh self regulated learning terhadap prestasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di SMK Negeri 5 Kota Bengkulu, 3) Mengetahui apakah ada pengaruh self control dan self regulated learning terhadap prestasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di SMK Negeri 5 Kota Bengkulu. Penelitian ini menggunakan jenis penelitian kuantitatif dengan pendekatan ex post facto. Populasi penelitian ini berjumlah 564 siswa, sampel sebanyak 85 siswa. Teknik pengambilan sampel menggunakan probability sampling tipe proportionate stratified random sampling. Teknik pengumpulan data menggunakan angket, dokumentasi, dan observasi. Hasil penelitian menunjukkan bahwa : 1) Terdapat pengaruh yang signifikan antara self control (X1) terhadap prestasi belajar siswa pada mata pelajaran Pendidikan Agama Islam (Y) SMK Negeri 5 Kota Bengkulu. Hal ini dapat dilihat dari nilai thitung > ttabel (2,124 > 1,988) dengan koefisien regresi 0,134 yakni memberikan kontribusi sebesar 13,4% terhadap prestasi belajar siswa (Y), 2) Terdapat pengaruh yang signifikan antara self regulated learning (X2) terhadap prestasi belajar siswa pada mata pelajaran Pendidikan Agama Islam (Y) SMK Negeri 5 Kota Bengkulu. Hal ini dapat dilihat dari nilai thitung > ttabel (1,997 > 1,988) dengan koefisien regresi 0,114 yakni memberikan kontribusi sebesar 11,4% terhadap prestasi belajar siswa (Y), 3) Terdapat pengaruh yang signifikan antara self control (X1) dan self regulated learning (X2) terhadap prestasi belajar siswa (Y) SMK Negeri 5 Kota Bengkulu. Hal ini dapat dilihat dari nilai Fhitung > Ftabel (4,627 > 3,10) dengan koefisien determinasi 0,079 yakni memberikan kontribusi sebesar 7,9% terhadap prestasi belajar siswa (Y), atau dapat dilihat dari persamaan regresi linier berganda Y = 66,652 + 0,134X1 + 0,114X2 + 0,05.Kata Kunci : Self Control, Self Regulated Learning, Prestasi Belajar Siswa No HP/WA: 089611949833